2013
DOI: 10.1063/1.4799476
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Compton scattering studies of magneto-dielectric Ba(Co0.85Mn0.15)O3−δ

Abstract: ) with bonding angle of 90 . The magnetic spin momentum estimated by the magnetic Compton profiles (MCP) of the samples had similar temperature dependence as that determined by the temperature dependence of magnetic moment by superconducting quantum interference device, which meant that the observed magnetic moments could be ascribed to the spin moment. The shapes of the MCPs of the samples were completely same regardless of the temperature measured. This result indicates that there are no changes of the momen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In these materials, the two kinds of 3d magnetic ions may have different d-electron numbers as well as chemical bonding across an oxygen ion at different angles. [7][8][9][10][11][12][13][14][15][16] In this case, we chose Mn-doped BaCoO 3 as it has a strong correlation between the structural and magnetic properties as well as a strong dependence on the amount of Mn substitution. 7,14,16) We found that the crystal structure of Ba(Co 1−x Mn x )O 3 (BCMO) ceramics changed from 2H-to 10H-via the 12H-type hexagonal phase depending on the composition ratio x, and the 12H-type phase exhibited ferrimagnetic ordering attributed to the ferromagnetic superexchange coupling of Co 4+ (d 5 )-O 2− -Mn 4+ (d 3 ) at a bonding angle of 180°.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these materials, the two kinds of 3d magnetic ions may have different d-electron numbers as well as chemical bonding across an oxygen ion at different angles. [7][8][9][10][11][12][13][14][15][16] In this case, we chose Mn-doped BaCoO 3 as it has a strong correlation between the structural and magnetic properties as well as a strong dependence on the amount of Mn substitution. 7,14,16) We found that the crystal structure of Ba(Co 1−x Mn x )O 3 (BCMO) ceramics changed from 2H-to 10H-via the 12H-type hexagonal phase depending on the composition ratio x, and the 12H-type phase exhibited ferrimagnetic ordering attributed to the ferromagnetic superexchange coupling of Co 4+ (d 5 )-O 2− -Mn 4+ (d 3 ) at a bonding angle of 180°.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] In this case, we chose Mn-doped BaCoO 3 as it has a strong correlation between the structural and magnetic properties as well as a strong dependence on the amount of Mn substitution. 7,14,16) We found that the crystal structure of Ba(Co 1−x Mn x )O 3 (BCMO) ceramics changed from 2H-to 10H-via the 12H-type hexagonal phase depending on the composition ratio x, and the 12H-type phase exhibited ferrimagnetic ordering attributed to the ferromagnetic superexchange coupling of Co 4+ (d 5 )-O 2− -Mn 4+ (d 3 ) at a bonding angle of 180°. The 2H-and 10H-type phases exhibited antiferromagnetic ordering attributed to the antiferromagnetic super-exchange couplings of Co 4+ (d 5 )-O 2− -Co 4+ (d 5 ) and Co 4+ (d 5 )-O 2− -Mn 4+ (d 3 ), respectively, at a bonding angle of 90°.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation